Central nervous system manifestations of tuberous sclerosis complex. Issue 3 (19th September 2018) - Lu, Derek S.; Karas, Patrick J.; Krueger, Darcy A.; Weiner, Howard L.
Abstract : Tuberous sclerosis complex (TSC) is a neurocutaneous autosomal‐dominant genetic syndrome marked by development of hamartomatous lesions arising from dysfunction of the mammalian target of rapamycin (mTOR) pathway. Although TSC remains a heterogeneous clinical entity, the recent inclusion of genetic diagnostic criteria reflects advancement in our understanding of its underlying etiopathogenesis. Abnormal cellular growth, differentiation, and migration result in multisystem sequelae, with neurologic manifestations of TSC representing the primary cause of morbidity and mortality for the majority of individuals. Modern imaging techniques aid in the diagnosis of TSC and guide treatment strategies by revealing central nervous system findings. Cortical tubers are the namesake lesion of the disorder and occur in up to 90% of cases, often exerting significant epileptogenic potential. Subependymal nodules are found in 80% of patients as calcified tumors lining the ependyma of the lateral ventricles. In some cases, these nodules are thought to progress to subependymal giant cell astrocytomas and may present with obstructive hydrocephalus. Retinal astrocytic hamartomas are also common, present in 50% of patients. Surgery remains the treatment of choice for large or symptomatic lesions, though clinical trials have highlighted a potential role for mTOR pathway antagonism. A multidisciplinary approach is necessary for achieving optimal patient outcomes.